-4u-2(-u-15)=8(2u-9)

Simple and best practice solution for -4u-2(-u-15)=8(2u-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4u-2(-u-15)=8(2u-9) equation:


Simplifying
-4u + -2(-1u + -15) = 8(2u + -9)

Reorder the terms:
-4u + -2(-15 + -1u) = 8(2u + -9)
-4u + (-15 * -2 + -1u * -2) = 8(2u + -9)
-4u + (30 + 2u) = 8(2u + -9)

Reorder the terms:
30 + -4u + 2u = 8(2u + -9)

Combine like terms: -4u + 2u = -2u
30 + -2u = 8(2u + -9)

Reorder the terms:
30 + -2u = 8(-9 + 2u)
30 + -2u = (-9 * 8 + 2u * 8)
30 + -2u = (-72 + 16u)

Solving
30 + -2u = -72 + 16u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-16u' to each side of the equation.
30 + -2u + -16u = -72 + 16u + -16u

Combine like terms: -2u + -16u = -18u
30 + -18u = -72 + 16u + -16u

Combine like terms: 16u + -16u = 0
30 + -18u = -72 + 0
30 + -18u = -72

Add '-30' to each side of the equation.
30 + -30 + -18u = -72 + -30

Combine like terms: 30 + -30 = 0
0 + -18u = -72 + -30
-18u = -72 + -30

Combine like terms: -72 + -30 = -102
-18u = -102

Divide each side by '-18'.
u = 5.666666667

Simplifying
u = 5.666666667

See similar equations:

| 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g | | 6x-10-4x+13=-2 | | 15=s-(-4) | | 16-10/2 | | 9n^2+36n+20=0 | | a*6-1=10 | | 1,430/2=t/5 | | b-(-55)=62 | | 3/4x-1/3x=1/12 | | 5x+5+7x-8+4x-13+5x-2=360 | | 6c=-78 | | 5x-13=4x+5 | | 10=16 | | -3(2-3y)=2(1+5y) | | v/2 | | a^3c^2/9b | | x+4=10x-14 | | 4(3x+1)=5x+66 | | .5x+12.3=7.1-1.1x | | 28=3X-14 | | 4(x+x+7)-2x+8-4= | | T^3+8t^2+15t=0 | | 2X^2-7X+3=5 | | (-3-1/3x)^3 | | 2+0.5d=25 | | h=3+80t-16t^2 | | x^2+9=103 | | 5k-21=-3k+24 |

Equations solver categories